STUDI TENTANG ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MELANJUTKAN PENDIDIKAN PERGURUAN TINGGI DI WILAYAH PEGUNUNGAN - Mita Rositasari; Bayu Cahyoadi (STKIP Persada Khatulistiwa Sintang, 2025)
This research is based on the phenomenon of low interest in continuing education to higher education among young people in Pagerwojo District, Tulungagung. This primary research problem seeks to answer the question of what dominant factors influence the decision to continue studying and what intervention strategies are most effective in encouraging this interest. Using a qualitative descriptive approach, data were collected through in-depth interviest The results indicate that internal motivations, such as a strong desire to change one’s socioeconomic status, are dominant as driving factors. This motivation in reinforced by external factor, namely family financial support and the availability of scholarships, which have proven effective. However, this study also identified significant challenges that hinder this interest. These challenges include limited information from parents (often due to their own low level of education) and the pragmatic views of local communities that tend to judge success only from tangible and immediate results, rather than from the long-term educational process. The limitations of this research lie in its local and qualitative nature. These findings focus solely on the internal dynamics of Pagerwojo District and may not be broadly generalizable to other areas in Tulungagung or ther regions with different socio-econimic characteristics.